Repairing Distortion-Induced Fatigue Cracks in Steel Bridge Girders Using Angles-with-Plate Retrofit Technique. I: Physical Simulations - Alemdar, Fatih; Nagati, Daniel; Matamoros, Adolfo; Bennett, Caroline; Rolfe, Stan (ASCE-AMER SOC CIVIL ENGINEERS, 2014)
Physical simulations of 914 mm (36 in.) deep girder-cross frame subassemblies subjected to cyclic loading were carried out to study the effects of distortion-induced fatigue and to evaluate the effectiveness of a new retrofit measure. The new repair method consists of adding steel angles connecting the girder web to the cross frame transverse connection plate (CP), and a steel plate on the opposite side of the girder web. Parameters of the experimental study included the retrofit configuration and length of the fatigue cracks. Test results showed that the new angles-with-plate retrofit measure was effective in preventing fatigue crack reinitiation for both horseshoe-shaped cracks around the CP-to-web weld and cracks along the flange-to-web weld. When the retrofit measure was implemented, specimens were able to exceed the number of cycles equivalent to infinite fatigue life for AASHTO Fatigue Category A details without any measureable fatigue crack growth, regardless of crack configuration. A test trial was also carried out to measure fatigue crack reinitiation life of the web-gap region with undersized crack-arrest holes. Experimental results showed that, for the stress range imposed at the web-gap region of the specimens and the crack-arrest hole diameter evaluated, fatigue cracks reinitiated at 40,000 cycles, which was below the limit for AASHTO Fatigue Category E' details. (C) 2014 American Society of Civil Engineers.
Keywords: Fatigue; Distortion-induced fatigue; Steel; Girder; Bridge; Cross-frame; Repair; Retrofit; Metal and composite structures; Construction & Building Technology; Engineering